The adventures of Huckleberry Finn (The Adventures of Tom and Huck, ,, 2009)
A mischievous youth encounters a runaway slave and together they travel down the Mississippi in search of adventure, in the classic novel accompanied by essays by Van Wyck Brooks and Carl Van Doren.

Before now: a novel (Katherine Tegen Books, an imprint of Harpercollins Publishers, 2017)
Against all odds, Atty and Cole have escaped their lives in Minneapolis, leaving judgmental parents and unsavory circumstances behind. Their getaway was anything but clean, however, and both of them are haunted and hounded by the mistakes of their pasts.

Billion dollar girl (Razorbill, 2022)
After thirteen-year-old River Ryland is discovered to live mostly alone and a visit from Social Services goes horribly wrong, River runs away and a case of mistaken identity gives her the chance to life a live she never imagined.

Now you say yes (Peachtree Publishing Company Inc, 2021)
When her adoptive mother dies, fifteen-year-old Mari and is desperate to avoid being caught up in the foster system. Again. And to complicate matters, she is now the only one who can take care of her super-smart and on-the-spectrum nine-year-old stepbrother, Conor. Is there anyone Mari can trust to help them? Certainly not her mother's current boyfriend, Dennis. Not the doctors or her teachers, who would be obliged to call in social services. So in a desperate move, Mari takes Conor and sets out to find their estranged grandmother, hoping to throw themselves at the mercy of the only person who might take them in. On their way to New England, the duo experiences the snarls of LA traffic, the backroads of the Midwest, and a monumental stop in Missouri where they witness the solar eclipse, an event with which Conor is obsessed. Mari also learns about the inner workings of her stepbrother's mind and about her connections to him and to the world... and maybe even a little about her own place in it.

The only living boy: #3,Once upon a time (Only living boy, 3,, 2016)
"Twelve-year-old Erik Farrell ran away from home and woke up without his memory in a strange and dangerous new world..."--Page 4 of cover.

The only living boy: #1,Prisoner of the patchwork planet (Only living boy, 1, 1, 2016)
Tells the story of 12-year old Erik Farrell, who runs away from home only to find himself without his memory, stranded on a patchwork planet with danger lurking around every corner.
Vol. 1. Prisoner of the Patchwork Planet --

Adventures of Huckleberry Finn (Manga classics, ,, 2017)
"Chafed by the "sivilized" restrictions of his foster home, and weary of his drunkard father's brutality, 14 year-old Huck Finn fakes his own death and sets off on a raft down the Mississippi River. He is soon joined by Jim, an escaped slave. Together, they experience a series of rollicking adventures that have amused readers, young and old, for over a century. The fugitives become close friends as they weather storms together aboard the raft and spend idyllic days swimming, frying catfish suppers, and enjoying their independence. Their peaceful existence ends abruptly, however, with the appearance of the King and the Duke, an incorrigible pair of con artists who take over the raft. After many difficulties, Huck and Jim escape their tormentors, and with the help of an imaginative rescue by Huck's old friend Tom Sawyer, Jim gains his freedom. Manga Classics breathes new life into this American Classic with a faithful adaptation of Mark Twain s masterpiece."-- cover page 4.

The adventures of Tom Sawyer (Manga classics, ,, 2018)
"That rascal Tom Sawyer cant stay out of trouble for a single minute! In this tale full of childhood mischief, adventure, and trouble, Tom turns the Mississippi town of St. Petersburgh on its ear nearly every day but theres a darker side to this town as well. When his childish adventures take a deadly turn, Tom and his outcast friend, Huckleberry Finn, must find a way to rise to the challenge, or else&!